Preventing Stroke in AF: Current Issues - Mosley, Mary (MD Conference Express, 2014)
Atrial fibrillation (AF) increases the risk of stroke, and this risk is further increased in a linear fashion with higher CHADS2 scores (representing congestive heart failure; hypertension; age =75 years; diabetes mellitus; and prior stroke, transient ischemic attack, or thromboembolism) [Crandall ME et al. Pacing Clin Electrophysiol 2009]. This article discusses catheter ablation (CA) to lower the risk of stroke in AF patients, echocardiographic contraindications for cardioversion, and the use of remote device monitoring to reduce stroke risk.